MIOCENE RIFTING OF FUERTEVENTURA (CANARY ISLANDS) - Fernandez C.; Casillas R.; Navarro E.G.; Gutiérrez M.; Camacho M.A.; Ahijado A. (My University, 2006)
The older geological units of the volcanic island of Fuerteventura (Canary Islands), i.e., the so-called basal complex and the lower part of the subaerial volcanic rocks, show abundant structures indicative of a long-lived period of Miocene tectonic activity. These structures include faults, dike swarms, kilometer-scale folds, tilted sequences, and fissurai and central volcanic edifices. A detailed structural study, based on geological mapping and the use of fault slip inversion techniques and statistical analysis of dike orientation, has allowed the identification of three separated Miocene deformation phases: M-D1, M-D2, and M-D3. The average extension directions determined for these phases are NW-SE, NNE-SSW, and ENE-WSW, respectively. A model of oceanic lithosphere rifting is proposed to account for this deformation history. A buoyant, anomalous sublithosphere mantle triggered the extension in the lithosphere beneath Fuerteventura, isolating it during the early and middle Miocene from the plate-scale collision regime predominant in the NW comer of the African plate. Copyright 2006 by the American Geophysical Union.
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен